Quantification of retinoid concentrations in human serum and brain tumor tissues - Ali, Ramadan Mahmoud Mohamed; Campos, Benito; Dyckhoff, Gerhard; Haefeli, Walter E.; Herold-Mende, Christel; Burhenne, Jürgen (Analytica chimica acta, 2012)
Retinoic acid signaling is essential for central nervous system (CNS) differentiation and appears to be impaired in tumors. Thus far, there are no established methods to quantify relevant retinoids (all-trans-retinoic acid, 9-cis-retinoic acid, 13-cis retinoic acid, and retinol) in human brain tumors. We developed a single step extraction and quantification procedure for polar and apolar retinoids in normal tissue, lipid-rich brain tumor tissues, and serum. This quantification procedure is based on high performance liquid chromatography (HPLC) with diode-array detection (DAD) using all-trans-acitretin as an internal standard and extraction by liquid-liquid partition with ethyl acetate and borate buffer at pH 9. Recovery with this extraction procedure was higher than earlier (two-step) liquid-liquid extraction procedures based on hexane, NaOH, and HCl. The overall quantification procedure was validated according to Food and Drug Administration (FDA) guidelines and fulfilled all criteria of accuracy, precision, selectivity, recovery, and stability. The overall method accuracy varied between −5.6% and +5.4% for serum and −3.8% and +6.2% for tissues, and overall precision ranged from 3.1% to 6.9% for serum and 2.1% to 8.3% for tissues (%CV batch-to-batch). The lower limit of quantification for all compounds in tumor tissue (and serum) was 3.9ngg−1 (ngmL−1). Using this assay, photodegradation of the retinoids was evaluated and endogenous polar and apolar retinoids were quantified in sera and brain tumor tissues of patients and compared with serum and tonsil tissue concentrations of controls. It may thus serve as a suitable method for the characterization of retinoid uptake and metabolism in the respective compartments.
Gesehen am 25.04.2018